A Risk-Based Screening Approach to Patients Needing Surgery During the De-Escalation Phase of COVID-19 Pandemic. (April 2021) - Vilallonga, Ramon; Pellino, Gianluca; Almirante, Benito; Domínguez González, José Manuel; Blanco-Colino, Ruth; Petrola, Carlos; Armengol, Manel
Since the outbreak of COVID-19 pandemic, many national and international surgical societies have produced guidelines regarding the management of surgical patients. During the mitigation phase of the pandemic, most documents suggested to consider postponing elective procedures, unless this might have impacted the life expectancy of patients. As awareness and knowledge about COVID-19 are gradually increasing, and as we enter a phase when surgical services are resuming their activities, surgical strategies have to adapt to this rapidly evolving scenario. This is particularly relevant when considering screening policies and the associated findings. We herein describe a risk-based approach to the management of patients with surgical diseases, which might be useful in order to limit the risks for healthcare workers and patients, while allowing for resuming elective surgical practice safely.